(The Influence of Reflux Ratio on Isolation of Alpha-Pinene by Fractional Distillation) - Achmad Moestafa (Warta Industri Hasil Pertanian, 1988)
Alpha pinena is the main component of turpentine oil. This compound is very important since its derivates are used in various indutsries. It may be transformed into borneol, iso-borneol, citronellol and geraniol through an acid reaction which are used in parfumery or it mey be oxidised to pinic and pinonic acid which are used in polymer industry. The isolation of a-pinena from turpentine oil has long been know for centuries, unfortunately no one has discussed it in detail. The aim of this experiments is to find out a suitable condition during the isolation especially the value of reflux ratio if a fractional distillation process is undertaken. By using an Oldershaw type fractional column equipped with five perforated plates it was found that 1:3 ratio was the optimum condition. Not less than 80% of a-pinena with 96% purity had been isolated by this method from a commercial turpentine oil.